(untitled) (Malaysian Journal of Civil Engineering, 2018)
Assessment of the qualitative performance of a roundabout in relation to factors, such as delays, queues, level of service (LOS), accident, operation cost and environmental issues is necessary for its successful operation. This study, therefore, aims at analysing the qualitative performance of roundabouts in an urban area, Nigeria with the Fate roundabout in Ilorin metropolitan city as study case. The movement of the vehicles was observed and traffic counts carried out manually, at 15 minutes intervals for 12 hours (6:30am-6:30pm) daily for seven (7) days, from Monday, June 15th to Sunday, June 21st, 2015. Results show that, the five (5) working days (Monday-Friday), have high traffic volume counts and were selected for the analysis. Peak hour factors (PHF) were used to convert the demand volumes to flow rates. The qualitative performance analyses were carried out based on the 12-step approach for the performance analysis of a roundabout as outlined by the Highway Capacity Manual. Approach and entry capacities were determined as mathematical functions of critical headway, and follow-up headway were then estimated using the analytical approach. The degree of saturation, delay, and queue length used in estimating the performance of a roundabout were also determined. The relation between the roundabout performance measure and capacity, expressed in terms of degree of saturation shows that the performance of the Fate roundabout ranged between LOS A – E. An increase in the entry lane width at Basin road approach was recommended to ensure continuous and smooth flow at the roundabout.